Dampak Gadget Terhadap Perkembangan Anak Usia Dini - Nor Annisa; Noor Padilah; Reni Rulita; Renny Yuniar (Publikasi Indonesia, 2022)
The development of technology is a challenge to the development of children. The use of gadgets for early childhood development can have an impact on the growth and development of early childhood both physically and mentally. The impact can be in the form of positive or negative influence on children's development. The purpose of this study was to find out how the use of gadgets in early childhood and how the positive and negative impacts on the use of gadgets. This research is entirely based on literature review or literature study. The data collected and analyzed are entirely derived from literature and other documentation materials, such as writings in books, research journals, and other media that are relevant and still under review. The results of this study explain that the use of gadgets correctly and correctly by early childhood will be a stimulation medium that is able to optimize aspects of child development. Excessive and unsupervised use of gadgets will also be bad for children's development in the future. So it is very important the role of parents to supervise, control and pay attention to all children's activities to see better child development.